Pengembangan Media Video Animasi Muatan Pelajaran Matematika Kelas III Sekolah Dasar - Vina Anggraini (Jurnal IKA PGSD (Ikatan Alumni PGSD) UNARS, 2021)
This research is motivated by the difficulty of learning mathematics on fractional material in determining the denominator and numerator. Efforts to overcome these problems, efforts are needed to develop learning media in the form of animated video media. This study aims to produce valid, practical and effective animated video media for the content of third grade elementary school mathematics. This type of research is development research, which uses a 4-D development model consisting of the stages of defining, designing, developing, and distributing. The results showed that the results of content validity obtained an average score of 84.5%, an average score of 84.3% construction validity, and an average score of 81.9% of language validity, then the average score of the validity of the three aspects is 80.4% with a very valid category, meaning that animated videos are suitable for use by teachers and students. The results of the practicality assessment carried out by teachers and students of class III obtained an average score of 90.9% with a very practical category, meaning that animated videos make it easier for teachers and students in learning. The results of the effectiveness of animated video media are supported by an assessment of student learning outcomes in the form of test questions with an average percentage of classical completeness scores of 81.25% with a very effective category, meaning that animated videos can help students achieve learning goals.